Effectiveness of medicinal plant essential oils on drug-resistant bacteria in Iran: A systematic review - Iman Khahan-Yazdi; Mohammadamin Shabani; Mohammadhassan Tajvidi-Monfared; Hassan Vahidi Emami; Faraz Mojab; Saeed Shams ‎; Zahra Taheri Kharameh (Institue of Medicinal Plants, ACECR, 2023)
Background: The efficacy of common antibiotics has been hindered by the emergence of drug resistance, including multidrug resistance (MDR). As a result, there is a growing interest in exploring alternative treatments for drug-resistant infections. One promising avenue is the use of herbal medicine, which possesses antimicrobial properties and may serve as a viable supplement or alternative to conventional antibiotics. Objective: This study aimed to determine the effectiveness of plant essential oils in Iran against drug-resistant bacteria. Methods: In this systematic review, we searched for keywords including herbal medicine, essential oil, Acinetobacter spp, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, and Enterococcus species in Scopus, PubMed, Web of Science, and internal databases. Articles published up to October 4, 2023, were considered without any time limit. Results: The results showed that the majority of studies conducted were related to thyme, and the most tested bacterial species were methicillin-resistant Staphylococcus aureus (MRSA) strains. Thyme exhibited the highest antibacterial activity, with the lowest minimum inhibitory concentration (MIC) equal to 0.31 µg/ml, followed by Oliveria decumbens with a MIC of 0.625 µg/ml. Conclusion: Herbal medicines may offer an efficient treatment option for antibiotic-resistant bacteria. However, further studies are needed to investigate potential adverse effects, antibacterial properties, and possible synergistic effects with other medicinal plants.